2017
DOI: 10.1038/oncsis.2017.35
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of miR-483-3p by the O-linked N-acetylglucosamine transferase links chemosensitivity to glucose metabolism in liver cancer cells

Abstract: The miR-483-3p is upregulated in several tumors, including liver tumors, where it inhibits TP53-dependent apoptosis by targeting the pro-apoptotic gene BBC3/PUMA. The transcriptional regulation of the miR-483-3p could be driven by the β-catenin/USF1 complex, independently from its host gene IGF2, and we previously demonstrated that in HepG2 hepatoblastoma cells carrying wild-type TP53 the upregulation of the miR-483-3p overcomes the antitumoral effects of the tumor-suppressor miR-145-5p by a mechanism involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Moreover, they identified that cellular glucose availability is participated in the regulation of miR-483-3p and demonstrated OGT activity as a molecular mechanisms link between miR-483-3p expression and glucose. Combined with their earlier research results, the glucose/OGT/miR-483-3p signaling pathway plays a vital part in the tumorgenic mechanisms of liver cancer and may involve in the drug resistance 68 . The DLC-1 gene has been revealed as a candidate tumor suppressor, and in colorectal cancer, miR-483-3p contributes to cancer cells proliferation via suppressing its target DLC-1 gene 23 .…”
Section: The Pathways and Interactions Of Mir-483 Involved In Digestimentioning
confidence: 75%
“…Moreover, they identified that cellular glucose availability is participated in the regulation of miR-483-3p and demonstrated OGT activity as a molecular mechanisms link between miR-483-3p expression and glucose. Combined with their earlier research results, the glucose/OGT/miR-483-3p signaling pathway plays a vital part in the tumorgenic mechanisms of liver cancer and may involve in the drug resistance 68 . The DLC-1 gene has been revealed as a candidate tumor suppressor, and in colorectal cancer, miR-483-3p contributes to cancer cells proliferation via suppressing its target DLC-1 gene 23 .…”
Section: The Pathways and Interactions Of Mir-483 Involved In Digestimentioning
confidence: 75%
“…Interestingly, it has been reported that mature miR-483-3p is upregulated in some types of tumours [32], but downexpressed in others [33]. For example, silencing of miR-483-3p promotes acquired gefitinib resistance and EMT in EGFR-mutant NSCLC by targeting integrin b3 [34], whereas glucose uptake increases the expression of the oncogenic miR-483-3p through the OGT pathway in liver cancer cells [17], suggesting that miR-483-3p may have complicated cancer-type specific functions. However, whether miR-483-3p is involved in oxaliplatin resistance has not been elucidated in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we comparatively assessed differentially expressed miRNAs and genes of HCT116 and HCT116/L cells with the final aim of clarifying the miRNAs and their target genes associated with oxaliplatin resistance. Previous studies have suggested that miR-483-3p was dysregulated in some types of tumours [17][18][19]. However, the mechanisms by which miR-483-3p is associated with oxaliplatin resistance in CRC are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…OGT silencing increases the sensitivity to 5-FU of BCG-823 gastric cancer cell line by enhancing expression of p53 upregulated modulator of apoptosis (PUMA) and caspase-3 pro-apoptotic proteins [ 159 ]. In this sense, Pepe et al showed in HepG2 hepatoblastoma cells that OGT stabilizes the transcriptional complex β-catenin/upstream stimulatory factor 1 (USF1) at the promoter of miR-483-3p, a microRNA responsible for transcription downregulation of PUMA [ 160 ]. Treatment with 2-deoxy-D-glucose (2-DG), a glucose-mimic inhibitor of glycolysis, reduces miR-483-3p expression and increases sensitivity to 5-FU-induced apoptosis.…”
Section: Glycosylation Alterations In Colorectal Cancer Cells and Resmentioning
confidence: 99%